Taphrorychus hirtellus Eichhoff (Curculionidae: Scolytinae, Dryocoetini) a new species to the Italian fauna, with a key to the Taphrorychus species of Europe - Cresta, Eleonora; Faccoli, Massimo; Giarruzzo, Federica; Siero, Emanuele Di; Ruzzier, Enrico; Sora, Nicolò Di; Speranza, Stefano (Zootaxa, 2025)
Taphrorychus hirtellus Eichhoff (Coleoptera, Curculionidae, Scolytinae), a European scolytine beetle previously documented in Central and Southeastern Europe, Turkey (type locality), and Algeria, is recorded for the first time in Italy. Specimens were collected in April and May 2021 in the Circeo National Park (Latium Region, central Italy) in multifunnel traps baited with a blend of quercivorol, α-copaene, ethanol and α-pinene. The species, considered native, is a new addition to the Italian fauna. In addition to the faunistic record, an identification key to the European Taphrorychus species is provided.